The role of social-psychological factors in the adoption of push-pull technology by small-scale farmers in East Africa: Application of the theory of planned behavior - Denis Waiswa; Beatrice Wambui Muriithi; Alice W. Murage; Dave Mwangi Ireri; Fredah Maina; Frank Chidawanyika; Fahri Yavuz (Heliyon)
Push-pull technology (PPT) continues to gain relevance among smallholder farmers across the East African region in managing the constraints affecting cereal crop yields including stemborers, fall armyworm, striga weed, and low soil fertility. While previous research has emphasized the significance of socioeconomic factors in explaining farmers' decisions to adopt PPT, the social-psychological factors that influence farmers' adoption intentions have not been extensively studied. Therefore, this study investigated the influence of social-psychological factors on the intention to adopt or increase the land area under PPT based on the theory of planned behavior (TPB). Moreover, this study extends the applicability of the TPB by incorporating an additional construct that addresses practical limitations within adoption decision-making, and providing evidence of how TPB constructs function differently across distinct agricultural contexts. Nine hundred and seventy-one (971) cereal growers comprising PPT users and non-users were interviewed in Kenya, Uganda, Tanzania, and Rwanda using a structured questionnaire. Utilizing the Partial Least Square-Structural Equation Modelling (PLS-SEM) and Artificial Neural Network (ANN), this study revealed a significant positive influence of TPB conceptual elements attitudes, subjective norms, and perceived behavioral control on farmers’ intentions to adopt or expand the land area under PPT. Additionally, the study found that the added construct “perceived limitations” negatively impacts these intentions. The results indicated significant variations in the impact of TPB constructs on the intentions to adopt and expand land under PPT across the studied countries. These insights underscore the need for tailored, context-sensitive interventions that integrate behavioral, social, and practical considerations. Additionally, understanding the country-specific determinants allows for more targeted policy measures, extension services, and support programs that can enhance the adoption and effectiveness of PPT, ultimately improving agricultural outcomes and livelihoods of farmers in this region.